Limits of teacher delivered sex education: interim behavioural outcomes from randomised trial. Issue 7351 (15th June 2002) - Wight, Daniel; Raab, Gillian M; Henderson, Marion; Abraham, Charles; Buston, Katie; Hart, Graham; Scott, Sue
Abstract: Objective: To determine whether a theoretically based sex education programme for adolescents (SHARE) delivered by teachers reduced unsafe sexual intercourse compared with current practice. Design: Cluster randomised trial with follow up two years after baseline (six months after intervention). A process evaluation investigated the delivery of sex education and broader features of each school. Setting: Twenty five secondary schools in east Scotland. Participants: 8430 pupils aged 13-15 years; 7616 completed the baseline questionnaire and 5854 completed the two year follow up questionnaire. Intervention: SHARE programme (intervention group) versus existing sex education (control programme). Main outcome measures: Self reported exposure to sexually transmitted disease, use of condoms and contraceptives at first and most recent sexual intercourse, and unwanted pregnancies. Results: When the intervention group was compared with the conventional sex education group in an intention to treat analysis there were no differences in sexual activity or sexual risk taking by the age of 16 years. However, those in the intervention group reported less regret of first sexual intercourse with most recent partner (young men 9.9% difference, 95% confidence interval −18.7 to −1.0; young women 7.7% difference, −16.6 to 1.2). Pupils evaluated the intervention programme more positively, and their knowledge of sexual health improved. Lack of behavioural effect could not be linked to differential quality of delivery of intervention. Conclusions: Compared with conventional sex education this specially designed intervention did not reduce sexual risk taking in adolescents.